Nutritional biomarkers: Current view and future perspectives. Issue 18 (12th December 2018) - Pande, Shubhra; Kratasyuk, Valentina A.; Medvedeva, Nadezhda N.; Kolenchukova, Oxana A.; Salmina, Alla B.
ABSTRACT: There is a poor relationship between nutrient intake and existing nutritional biomarkers due to variety of factors affecting their sensitivity and specificity. To explore the impact of nutrients at molecular level and devising a sensitive biomarker, proteomics is a central technology with sirtuins as one of the most promising nutritional biomarker. Sirtuins (seven mammalian sirtuins reported so far) have been reported to perform protein deacetylases and ADP-ribosyltransferases activity. It is distributed in different cellular compartments thereby controlling several metabolic processes. Sirtuins are oxidized nicotinamide adenine dinucleotide dependent, which implicates a direct effect of the metabolic state of the cell on its activity. Calorie restriction upregulates the mammalian sirtuin protein levels in variety of tissues and organs where it acts upon both histone and nonhistone substrates. Sirtuin senses nutrient availability and impacts gluconeogenesis, glycolysis, and insulin sensitivity. It deacetylates and inhibits the nuclear receptor that activates fat synthesis and adipogenesis in the body, leading to fat loss and bringing favorable cellular and health changes. Sirtuins mediates intracellular response that promotes cell survival, DNA damage repair thereby increasing the cell longitivity. The activation of sirtuins brings a wide spectrum of other health benefits and its activity levels are indicative of nutritional status as well as disease progression in cancer, inflammation, obesity, cardiovascular diseases, and viral infections. There are several foods that activate sirtuin activity and offer significant health benefits by their consumption.